2012
DOI: 10.3928/01477447-20120525-18
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of Heterotopic Ossification Following Major Elbow Trauma

Abstract: Heterotopic ossification is a common complication of Orthopaedic Trauma Association (OTA) type C distal humerus fractures and ulnohumeral fracture dislocations. The purpose of this study was to precisely define the incidence of heterotopic ossification following major elbow trauma and to identify risk factors for the development of clinically significant heterotopic ossification and for surgical excision of elbow heterotopic ossification.Current Procedural Terminology codes identified 156 patients who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…The first factor, longer time from injury to surgery, has previously been shown to associate with HO after elbow trauma [3,4,6,12]. We speculate that the delay often relates to referral of more complex fractures through the office or prioritizing in multiply injured patients.…”
Section: Repeat Irrigation and Débridement Of Deep Infectionmentioning
confidence: 82%
See 2 more Smart Citations
“…The first factor, longer time from injury to surgery, has previously been shown to associate with HO after elbow trauma [3,4,6,12]. We speculate that the delay often relates to referral of more complex fractures through the office or prioritizing in multiply injured patients.…”
Section: Repeat Irrigation and Débridement Of Deep Infectionmentioning
confidence: 82%
“…Previous studies [6,12,16], but not all [1,3], have also shown that dislocation correlates with restrictive HO. Complete ulnohumeral dislocation likely reflects greater soft tissue injury and a more severe injury, which in itself was identified as a predictor by Douglas et al [4]. Indeed, Foruria et al [6] recently showed that a prognostic model, which included injury-related factors for open fracture, elbow instability, and chest injury, was able to discriminate between patients with and without restrictive HO.…”
Section: Repeat Irrigation and Débridement Of Deep Infectionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previously, delay in treatment time between the injury and operative intervention has been noted to be related to formation of HO after these injuries. [5][6][7]13 Because many patients who develop HO require secondary surgical release or excision to regain motion and function, the development of HO can have a dramatic impact on outcome as well as the added burden of additional procedures. The ability to identify patients at risk for HO formation after elbow fracture-dislocations may be helpful in guiding treatment protocols.…”
mentioning
confidence: 99%
“…Complications following these injuries are common, with reported rates of infection ranging from 11% to 21%, neurovascular injury from 0% to 50%, nonunion from 8% to 21% [4-6], and heterotopic ossification (HO) in 0-35% [7][8][9][10][11][12][13][14][15]. Prior case series of <30 extremities have demonstrated improved outcomes and decreased complications based on the surgical approach [5] type of fixation [16], and tim\ing of surgical stabilization [5,17].…”
mentioning
confidence: 99%